Current status of cytopathology practices in Korea: annual report on the Continuous Quality Improvement program of the Korean Society for Cytopathology for 2018 - Chong, Yosep (J Pathol Transl Med, 2020)
BACKGROUND: The Korean Society for Cytopathology has conducted the Continuous Quality Improvement program for cytopathology laboratories in Korea since 1995. In 2018 as part of the program, an annual survey of cytologic data was administered to determine the current status of cytopathology practices in Korea. METHODS: A questionnaire was administered to 211 cytopathology laboratories. Individual laboratories submitted their annual statistics regarding cytopathology practices, diagnoses of gynecologic samples, inadequacy rates, and gynecologic cytology-histology correlation review (CHCR) data for 2018. In addition, proficiency tests and sample adequacy assessments were conducted using five consequent gynecologic slides. RESULTS: Over 10 million cytologic exams were performed in 2018, and this number has almost tripled since this survey was first conducted in 2004 (compounded annual growth rate of 7.2%). The number of non-gynecologic samples has increased gradually over time and comprised 24% of all exams. The overall unsatisfactory rate was 0.14%. The ratio of the cases with atypical squamous cells to squamous intraepithelial lesions accounted for up to 4.24. The major discrepancy rate of the CHCR in gynecologic samples was 0.52%. In the proficiency test, the major discrepancy rate was approximately 1%. In the sample adequacy assessment, a discrepancy was observed in 0.1% of cases. CONCLUSIONS: This study represents the current status of cytopathology practices in Korea, illustrating the importance of the Continuous Quality Improvement program for increasing the accuracy and credibility of cytopathologic exams as well as developing national cancer exam guidelines and government projects on the prevention and treatment of cancer.